A companion to Baugh and Cable's History of the English language - Cable, Thomas, 1942- (Routledge, 2002)
This comprehensive and accessible student workbook accompanies the fifth edition of Albert C. Baugh and Thomas Cable's 'History of the English Language'. Each chapter in the workbook corresponds directly to a chapter in the textbook and offers exercises, review questions, and other information.